A case of meningitis due to Listeria monocytogenes. Issue 5 (September 1961) - Beck, A.
Abstract : A case of meningitis due to Listeria monocytogenes is reported. The source and mode of infection could not be ascertained. The patient recovered after treatment with chlortetracycline.